2019
DOI: 10.1186/s12884-019-2654-3
|View full text |Cite
|
Sign up to set email alerts
|

Top research priorities for preterm birth: results of a prioritisation partnership between people affected by preterm birth and healthcare professionals

Abstract: BackgroundWe report a process to identify and prioritise research questions in preterm birth that are most important to people affected by preterm birth and healthcare practitioners in the United Kingdom and Republic of Ireland.MethodsUsing consensus development methods established by the James Lind Alliance, unanswered research questions were identified using an online survey, a paper survey distributed in NHS preterm birth clinics and neonatal units, and through searching published systematic reviews and gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…The miscarriage PSP had 1093 participants in round one, of which only 9.5% were healthcare professionals; the endometriosis PSP achieved 20% healthcare professional participation, of which 15% had experienced the condition themselves. 22 Likewise, as in this project, the cross over between healthcare professionals and patients was notable in other women’s health conditions, such as 11% in the preterm birth PSP 23 and 31% in the pessary use for prolapse PSP. 24 The high level of patient engagement was anticipated by the authors as the patient population for this condition has previously demonstrated a strong interest for taking part in research with hundreds or even thousands of responses on surveys in a matter of days.…”
Section: Discussionmentioning
confidence: 79%
“…The miscarriage PSP had 1093 participants in round one, of which only 9.5% were healthcare professionals; the endometriosis PSP achieved 20% healthcare professional participation, of which 15% had experienced the condition themselves. 22 Likewise, as in this project, the cross over between healthcare professionals and patients was notable in other women’s health conditions, such as 11% in the preterm birth PSP 23 and 31% in the pessary use for prolapse PSP. 24 The high level of patient engagement was anticipated by the authors as the patient population for this condition has previously demonstrated a strong interest for taking part in research with hundreds or even thousands of responses on surveys in a matter of days.…”
Section: Discussionmentioning
confidence: 79%
“…This is in contrast to the established increased prevalence of GBS at the time of preterm delivery 57 . To our knowledge, however, the effect of treatment of GBS on risk of PTB has not been evaluated recently, although this did rank highly in a recent research prioritisation project 58 . An programme of GBS vaccine development is currently underway and the effect upon PTB risk will be an interesting end point 59 …”
Section: Should We Offer An Assessment Of Vaginal Flora In Asymptomatmentioning
confidence: 97%
“…The prediction and prevention of labour before term was voted as the top research priority in PTB in two large UK research priority-setting projects involving service users and healthcare professionals. 58,103 All 24 of the areas of uncertainty identified by members of the preterm clinical Box ‱ Summary of research questions What effect will implementing known or suggested risk-reducing interventions for the prevention of preterm birth have on current population rates of preterm birth?…”
Section: Research Prioritiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the establishment of the JLA in 2004, this methodology has been used to identify the top 10 research questions in areas such as asthma, 18 miscarriage 19 and hyperacusis. 20 Other JLAs have addressed research priorities in pregnancy complications such as preterm birth 21 and stillbirth 22 but these did not have a focus on hypertensive disorders of pregnancy. A Canadian PSP focused on hypertension, but pregnancy did not feature in their top 25 questions.…”
Section: Open Accessmentioning
confidence: 99%